2017
DOI: 10.12693/aphyspola.132.81
|View full text |Cite
|
Sign up to set email alerts
|

EPR and Impedance Measurements of Graphene Oxide and Reduced Graphene Oxide

Abstract: We report the observations of electron paramagnetic resonance and impedance measurements of graphene oxide and reduced graphene oxide performed in the wide temperature range in order to get insight into the electronic properties of graphene-based materials and the role of oxygen functionalities in the charge carrier transport phenomena. In such systems the strong spin localization, hopping charge carrier transport as well as the formation of adsorption layers are observed, all the phenomena changing significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It is known that the ESR signal from GO is well observed at room temperature, but the ESR signal of reduced GO can be observed only below 100 K [18]. Since our samples of GO are reduced (contain a small amount of hydroxyl and carboxylic groups), this guarantees the absence of additional lines from our GO in the ESR spectra.…”
Section: Characterization Of the Erythrocyte Suspension Aftermentioning
confidence: 84%
“…It is known that the ESR signal from GO is well observed at room temperature, but the ESR signal of reduced GO can be observed only below 100 K [18]. Since our samples of GO are reduced (contain a small amount of hydroxyl and carboxylic groups), this guarantees the absence of additional lines from our GO in the ESR spectra.…”
Section: Characterization Of the Erythrocyte Suspension Aftermentioning
confidence: 84%
“…Increasing the number of the paramagnetic centers as well as growing losses due to the cyclotron motion of conduction electrons in the external magnetic field B 0 change B 1 . Moreover, due to hygroscopic properties of GO water molecules can be adsorbed on its surface [33] and the proton conductivity of this material can be observed [6,34,35]. This conductivity as well as the molecular dynamics of the functional groups on the surfaces of GO and RGO result in the non-resonant losses and can also change B 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Graphene oxide (GO) is a well-known and widely used form of functionalized graphene [1,2]. Experimental studies of paramagnetic properties of this material have been reported [3][4][5][6][7][8]. The electron paramagnetic resonance (EPR) signals of GO and other graphene-related materials can be due to localized electrons, conduction electrons or their exchange coupled system [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an unusually strong temperature dependence of the intensity of the narrow EPR line in prGO was observed and explained by Anderson localization of conduction electrons in the strongly defected structure of graphene flakes . This type of localization in rGO was earlier deduced from impedance measurements in addition to the expected and more frequently observed Mott localization on graphene flakes. ,, …”
Section: Introductionmentioning
confidence: 84%
“…Moreover, conduction electrons mediate exchange interactions between isolated magnetic moments, which can lead to magnetic ordering. The preferential ordering in the graphene layer is antiferromagnetic in nature. , In contrast to a single exchange-narrowed EPR line, two or more lines in GO and rGO have been reported. ,,, Since at low density of conduction electrons not all PCs are exchange-coupled, uncoupled centers can manifest themselves in an overall spectrum by an additional EPR line. The observed narrower EPR line is associated with unpaired electrons localized at defects and edge states. , Attempts to distinguish between such PCs and conduction electrons were made assuming different temperature dependences of their signals in the continuous wave (CW) EPR .…”
Section: Introductionmentioning
confidence: 99%